2011
DOI: 10.1063/1.3586256
|View full text |Cite
|
Sign up to set email alerts
|

Highly p-doped epitaxial graphene obtained by fluorine intercalation

Abstract: Metal nanoantenna plasmon resonance lineshape modification by semiconductor surface native oxide J. Appl. Phys. 112, 044315 (2012) Asymmetric interfacial abruptness in N-polar and Ga-polar GaN/AlN/GaN heterostructures Appl. Phys. Lett. 101, 091601 (2012) On the mechanisms of energy transfer between quantum well and quantum dashes J. Appl. Phys. 112, 033520 (2012) Enhanced internal quantum efficiency in graphene/InGaN multiple-quantum-well hybrid structures

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
115
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 26 publications
2
115
2
Order By: Relevance
“…E-mail: Thomas.Seyller@physik.tu-chemnitz.de (Thomas Seyller) dependent [4] and it has been observed that this is a direct consequence of the presence of the buffer layer [10]. In recent years, various elements such as gold [11], lithium [12], silicon [13], fluorine [14], germanium [15], oxygen [16][17][18][19] and hydrogen [10,[20][21][22][23] have been intercalated between the buffer layer and SiC(0001) in order to modify the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: Thomas.Seyller@physik.tu-chemnitz.de (Thomas Seyller) dependent [4] and it has been observed that this is a direct consequence of the presence of the buffer layer [10]. In recent years, various elements such as gold [11], lithium [12], silicon [13], fluorine [14], germanium [15], oxygen [16][17][18][19] and hydrogen [10,[20][21][22][23] have been intercalated between the buffer layer and SiC(0001) in order to modify the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen is therefore a prime candidate for the future integration of quasi-free-standing graphene into devices. Fluorine, on the other hand, has been demonstrated to lead to exceptionally high p-type doping of the resulting graphene layer with a large hole concentration of 4.5×10 13 cm -2 [14].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The n-doping of "monolayer graphite" by intercalation of alkali metals was first demonstrated in 1994 by Nagashima et al, 23 and n-STD induced by alkalimetals intercalation in graphene and graphite has been studied in detail since then. 9,10,[24][25][26][27] Conversely, the pdoping of graphene with intercalated materials remained less explored until recently, when it was shown that it is possible to achieve a pronounced hole doping upon intercalation of graphene with fluorine 28 and chlorine. 29 Here we generalize the use of metal halides for p-doping of graphene, by studying aluminum bromide as an electron acceptor and intercalation agent.…”
mentioning
confidence: 99%
“…43,44 From the slope of the dispersion curve in Fig. 3, the value of v F , where v F is Fermi velocity, can be estimated as ∼6 eV·Å which, together with the Fermi level shift of ∼0.35 eV, yields 18,19,28 a hole concentration of n h 9×10 12 cm −2 for the brominated graphene (compared to 4.5 × 10 13 cm −2 and ∼ 3 × 10 13 cm −2 for fluorinated and chlorinated graphene, respectively 28,29 ). This estimation of the doping level in the graphene/AlBr 3 /Ir system is consistent with the assumption that the origin of the doping is a charge transfer to the more electronegative halide molecules of the intercalant material, given that electronegativity decreases in the row of halides from fluorides to bromides.…”
mentioning
confidence: 99%
See 1 more Smart Citation